PENGELOLAAN PEMBANGUNAN TAMBANG GALIAN C BERBASIS LINGKUNGAN DI LUBUK ALUNG KABUPATEN PADANG PARIAMAN - sumiati sumiati; Joni Fernandes (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2019)
Abstract The C-based mining management of the environment has an impact on the economy, social and environmental sustainability. This study aims to look empirically at the effect of the mining of C mining on the economic, social and environmental aspects. The object of this research is that the community is in the mining area. Samples taken using the convenience sampling method. The results showed that the economic variables had significant and positive effects on the management of quarrying c mines, socially had a positive and significant effect on the management of quarrying c mines and the environment had a positive and significant effect on the management of quarrying C mines. properly so that environmental damage can be minimized. Keywords: Quarry mine management c, economic, social and environment